Increasing Access to Credit through Reforming Secured Transactions in the MENA Region - Alvarez de la Campa, Alejandro (2012)
This paper provides a comparative summary of secured transactions systems related to the use of movable property as collateral in the MENA region vis a vis international practices in countries with modern secured transactions systems. The paper sets out the importance of introducing reforms in the area of secured transactions with the objective of increasing access to credit for businesses, particularly SMEs. The MENA region clearly lags behind all other regions in the introduction of secured transactions reforms. The paper summarizes many of the weaknesses common across the region. The two main critical areas that need urgent reforms are the creation of modern secured transactions laws and electronic movable collateral registries, and the need to improve enforcement mechanisms for security interests in movable property.